Digital economy and the rise of open cooperativism: the case of the Enspiral Network. (May 2017) - Pazaitis, Alex; Kostakis, Vasilis; Bauwens, Michel
This article explores how autonomous workers/contributors, involved in peer-to-peer relations, can organise their productive efforts so that they have sustainable livelihoods. The discussion is guided by the concept of 'open cooperativism', which argues for a synergy between the commons-based peer production movement and elements of the cooperative and solidarity economy movements. To this end, we review the case of Enspiral, a network of professionals and companies that empowers and supports social entrepreneurship. We explore its values, operation and governance as well as the chosen strategies for autonomy and sustainability. Finally, some lessons are summarised for the cooperative and union movement, which point to open cooperativism as an integrated vision.